ANILISIS IMAGE QUALITY CT SCAN THORAX DENGAN VARIASI LUNG WINDOW KERNEL PADA MSCT SIEMENS SOMATOM EMOTION 6 IMAGE QUALITY ANALYSIS CT SCAN THORAX LUNG WINDOWS WITH KERNEL VARIATIONS USING MSCT SIEMENS SOMATOM EMOTION 6 - Angga Yosainto Bequet; Yeti Kartikasari; Sri Mulyati; Susi Tri Isnoviasih (Jurnal Imejing Diagnostik (JImeD), 2019)
Background: To be able to show the Lung anatomy in detail in CT Scan Thorax lung window then required a sharp image quality. One way to improve image sharpness is to use kernel settings. The purpose of research is to know the difference of the quality of anatomical image with kernel variation CT Scan Thorax Lung Window and know the proper kernel selection to produce CT scan of thorax lung windows the bestMethods: Type of research is an experiment. The study was conducted using a CT image scan of thorax on axial lung window slices in cases of lung tumors in the kernel B50s, B60s, B70s, B80s, and U90s. The research was conducted by measuring the CT image quality of thorax scan on the windows lung by way of questionnaire assessment to 5 radiologist as the observer to CT Scan image to determine the level of clarity of anatomical criteria.Results: The results showed that there were significant differences in the quality of anatomical imagery with kernel variation of B50s, B60s, B70s, B80s, U90s with p-value 0.05. CT images can thorax lung windows that have the best anatomical image quality of the samples taken are shown by the use of the kernel U90s.Conclusions: There are significant differences in the quality of anatomical imagery with kernel variation of B50s, B60s, B70s, B80s, U90s. The kernel that generates image detail for CT thorax lung windows is the U90s kernel